The Emotions of the Outbreak. Topics, Sentiments and Politics on Twitter During Chilean October - Jara-Reyes, R; Faure-, A (Springer Science and Business Media Deutschland GmbH, 2022)
This paper interrogates the coherence and evolution of emotions circulating on Twitter in a specific context: the social and political outburst of October 2019 in Chile. Starting from the important literature that addresses the relationship between social movements, emotions and social networks, the paper asks about the particularities that this phenomenon in a country where the penetration and use of social networks is intense. By means of a sentiment analysis technique, more than 1,444,344 tweets published during a seven-week period are processed, putting particular interest in the description of the topics and emotions dumped in these messages. In the discussion we estimate how the exercise dialogues with results found in other similar situations, while in the conclusions we ponder its relevance for the analysis of emotions in situations of social conflict. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.